2006
DOI: 10.1055/s-2006-942272
|View full text |Cite
|
Sign up to set email alerts
|

Teratoma with Malignant Transformation: Experiences of the Cooperative GPOH Protocols MAKEI 83/86/89/96

Abstract: Malignant transformation of pure teratomas constitutes a very rare entity in children and adolescents that is most commonly observed in postpubertal girls with ovarian teratoma. Compared to adult patients, similar malignant entities can be observed in association with teratoma. However, in our series, no sarcoma was diagnosed. In localised tumors, complete resection appears to be adequate, whereas chemotherapy should be considered in patients with R1- or R2-resection. Cisplatinum-based chemotherapy was effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 18 publications
2
15
1
5
Order By: Relevance
“…The incidence of intratesticular vs. metastatic occurrence differs in different series, with 43 % of adult cases identified within the primary tumors and the remaining ones at the time of relapse or in the metastasis [29]. The morphology of the teratoma (mature vs. immature teratomas) does not have any impact on the risk of TMSC development [59]. Conventional cytogenetics has been used to demonstrate germ cell origin of these somatic malignancies arising in germ cell tumors [60], but to clarify the biology of TMSC; further studies at molecular level are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of intratesticular vs. metastatic occurrence differs in different series, with 43 % of adult cases identified within the primary tumors and the remaining ones at the time of relapse or in the metastasis [29]. The morphology of the teratoma (mature vs. immature teratomas) does not have any impact on the risk of TMSC development [59]. Conventional cytogenetics has been used to demonstrate germ cell origin of these somatic malignancies arising in germ cell tumors [60], but to clarify the biology of TMSC; further studies at molecular level are needed.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 In children and young adults, similar malignant entities can be observed in association with teratoma, but sarcomas appear to have not been observed. 4 Carcinoid tumors are rare, representing less than 6% of TMTs. 3,5 In adults, carcinoid tumors are considered as well-differentiated neuroendocrine tumors with low-grade malignancy, and their 5-year survival probability is 44%e56%, regardless of location.…”
Section: Discussionmentioning
confidence: 99%
“…14,35,36 The morphology of the teratoma (mature vs. immature) has no impact as a risk factor for the development of a somatic malignant tumor. 37 The conventional germ cell tumors show an excellent response to platinum-based chemotherapy, with an estimated 90% survival 11 ; however, those with malignant transformation show an aggressive behavior and propensity to systemic progression. In a study, Comiter et al reported an 81% range of recurrence in patients treated with surgical resection and platinum-based chemotherapy, with a median time to recurrence of 6 months.…”
Section: Discussionmentioning
confidence: 99%